Geographies of adult multigenerational family households in metropolitan Sydney. (21st December 2015) - Burnley, Ian; Liu, Edgar; Easthope, Hazel
Abstract: This paper investigates spatial trends of multigenerational adult families in metropolitan Sydney. Australia's immigrant gateway city, Sydney has high housing costs and infrastructure pressures, and planning policies support higher residential densities. In this context, the accommodation of persons living in multigenerational families is examined, by major region of origin, their geographies in Sydney, and by housing costs and constraints. Results highlight that cultural origins were influential in multigenerational household formations, and such formation is higher in areas of first and second ethnic community formation areas. Multigenerational living is also more common in middle ring and outer areas of cheaper housing. Implications are drawn for more nuanced housing policies in Sydney and comparable cities, given that detached and semi‐detached houses were favoured by these households, whereas two‐fifths of new housing constructed in Sydney in 2011 consists of two or less bedroom apartments.